Measurement of absolute γ-ray emission probabilities in the decay of 227Ac in equilibrium with its progeny. (February 2019) - Marouli, M.; Lutter, G.; Pommé, S.; Van Ammel, R.; Hult, M.; Pierre, S.; Dryák, P.; Carconi, P.; Fazio, A.; Bruchertseifer, F.; Morgenstern, A.
Abstract: The emission probabilities of γ rays produced in the 227 Ac decay series were determined by high-resolution γ-ray spectrometry of sources with standardised activity. The sources were prepared quantitatively on glass discs by drop deposition of a solution with 227 Ac in radioactive equilibrium with its daughter nuclides. Their activity was measured by a primary standardisation technique based on alpha-particle counting at a defined low solid angle. Four laboratories performed γ-ray spectrometry and derived absolute γ-ray intensities. Mean values were calculated and compared with literature data and the currently recommended evaluated data. New values on certain γ-ray emission probabilities are proposed. Highlights: Measured gamma-ray emission probabilities in 227 Ac decay series. Mean values taken from 4 laboratories. Source activity determined by primary standardisation. Results reported for 87 γ-ray lines. Generally in good agreement with literature values.